2008
DOI: 10.1016/j.ajhg.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Common Breast Cancer-Predisposition Alleles Are Associated with Breast Cancer Risk in BRCA1 and BRCA2 Mutation Carriers

Abstract: Germline mutations in BRCA1 and BRCA2 confer high risks of breast cancer. However, evidence suggests that these risks are modified by other genetic or environmental factors that cluster in families. A recent genome-wide association study has shown that common alleles at single nucleotide polymorphisms (SNPs) in FGFR2 (rs2981582), TNRC9 (rs3803662), and MAP3K1 (rs889312) are associated with increased breast cancer risks in the general population. To investigate whether these loci are also associated with breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 242 publications
(194 citation statements)
references
References 20 publications
12
176
3
3
Order By: Relevance
“…Multi-center, multi-national studies recently showed that such SNPs either did not modify the risk of breast cancer in BRCA1/2 mutation carriers or only modestly (eg, RR 1.1-1.3). 28,29 Xu et al analyzed the utility of the 14 SNPs associated with prostate cancer risk. 30 By themselves, the SNPs were not particularly helpful for identifying men who would go on to develop prostate cancer, as we have noted in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-center, multi-national studies recently showed that such SNPs either did not modify the risk of breast cancer in BRCA1/2 mutation carriers or only modestly (eg, RR 1.1-1.3). 28,29 Xu et al analyzed the utility of the 14 SNPs associated with prostate cancer risk. 30 By themselves, the SNPs were not particularly helpful for identifying men who would go on to develop prostate cancer, as we have noted in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…The Consortium of Investigators of Modifiers of BRCA1/2 has recently evaluated whether variants in FGFR2 (rs2981582), TNRC9 (rs3803662) and MAP3K1 (rs889312) are associated with the risk of BC in over 10 000 BRCA1 and BRCA2 mutation carriers from 23 studies (Antoniou et al, 2008). The evidence of association with SNP rs889312 in MAP3K1 was weaker and was restricted to BRCA2 mutation carriers, however, this SNP was not associated with an increased risk in BRCA1 carriers.…”
Section: Map3k1mentioning
confidence: 99%
“…Reasons for variation may include different mutations in the same gene (allelic variation) [5,[7][8][9], the effect of modifying genes [10][11][12], and non-genetic modifiers [13]. Several studies have indicated that the penetrance of BRCA1 and BRCA2 mutations has increased in recent generations [14][15][16], which supports the concept that non-genetic risk factors, of which the prevalence has increased, also affect the risk.…”
Section: Introductionmentioning
confidence: 99%